Path Relinking for a Constrained Simulation-Optimization Team Scheduling Problem Arising in Hydroinformatics - Nonato, Maddalena; Peano, Andrea (AIIA 2015 Advances in Artificial Intelligence, 2015)
We apply Path Relinking to a real life constrained optimization problem concerning the scheduling of technicians due to activate on site devices located on a water distribution network in case of a contamination event, in order to reduce the amount of consumed contaminated water. Teams travel on the road network when moving from one device to the next, as in the Multiple Traveling Salesperson Problem. The objective, however, is not minimizing travel time but the minimization of consumed contaminated water. This is computed through a computationally demanding simulation given the devices activation times. We propose alternative Path Relinking search strategies exploiting time-based and precedence-based neighborhoods, and evaluate the improvement gained by coupling Path Relinking with state of the art, previously developed, hybrid Genetic Algorithms. Experimental results on a real network are provided to support the efficacy of the methodology.